Women's community participation levels in community-based health programs regarding breast cancer prevention in Metropolitan Tehran, Iran - Ahmadian, Maryam; Redzuan, Ma'rof; Emby, Zahid; Abu Samah, Asnarulkhadi (Canadian Center of Science and Education, 2010)
Iran has recognized community participation in health research as an essential part of the country's health system. Community participation is focused on the prevention of communicable diseases, mother and child care, family planning and first aid. Besides, the issues of health education and community participation regarding breast cancer prevention are not similar to other activities included into primaiy health care services, such as family planning in Iran. Within this context, increasing the participation of women community regarding breast cancer prevention, through recognized channels such as health workers, community leaders, health educators, health care professionals, teachers and women volunteers should be given high priority at on the community, district, province and national levels. Local community participation in health and wellbeing is strongly supported as a fundamental element to development. Thus, the objective of the cuiTent study was to identify the levels of women's community participation in community-based program on breast cancer prevention. The study involves a cross sectional survey of women who have participated in mammography in the last two years (n=86). The actual level of community participation was assessed based on Rifkin's perspective. Using five levels of participation in health programs by Rifkin (1991), the study examined the feasibility of public participation in health and relieves effort on breast cancer prevention based on local community participation. The study assessed the level of women's community participation in breast cancer prevention programs, due to the importance of women's role in the community. Women's community participation in breast cancer prevention is currently insignificant. The maintenance of benefits and activities denotes sustainability in community -based health programs. More researches are therefore needed to understand the role of local communities in the development of community- based health programs.